Analytical Toolkit for Assessing Financial Security Risks of Companies in the Russian Construction Sector - N. A. Kazakova; A. K. Zavalishina (Финансы: теория и практика, 2024)
The construction sector today accounts for the largest volume of public procurement, bankruptcies and corporate fraud. Practice shows that the methods used to identify unscrupulous companies are not effective enough, which determines the relevance of the development of integrated risk assessment tools for financial security. In this regard, the purpose of the study was to substantiate the risk-factor approach to assessing and diagnosing financial security risks using a comprehensive analytical toolkit developed based on the concepts of industry analysis, professional auditing standards and financial reporting. The scientific novelty of the study is to integrate methods of assessment of financial security risks, the application of basic data processing technologies and flexible situation modeling with the possibility of adjusting models to a specific situation, taking into account identified industry risks. The theoretical significance of the study is represented by the concept of financial security as an aggregate result of the action of identified risk factors in the conditions of a highly turbulent economy, which served as a navigator for the development of an analytical tool that ensures consistency of the interpretation of the results at the stages of industry analysis, assessment of the likelihood of bankruptcy by logit-model and diagnosis of corporate fraud risks based on indicators of probability of distortion of financial statements. The practical value of the toolkit is the application of the international classification of financial risks, the selection of adequate, statistically significant indicators, calculated on the empirical basis of the financial statements of companies in the construction industry, downloaded from the Spark-Interfax information resource, which also proves the relevance of the results obtained and the possibility of using for the selection of organizations — potential participants in public procurement, in the audit practice, related audit services, arbitration practice, investment and banking to identify unscrupulous borrowers.